P.O.V : exploring truth and post-truth - Wong, Vanessa Faith Tze Yeung (Nanyang Technological University, 2021)
Post-truth is defined as ‘circumstances in which objective facts are less influential in shaping public opinion than appealing to emotion and personal belief’. It has, however, always existed in our society and remains an issue to this day. Although it is almost impossible to completely resolve this century-old problem, we can start by spreading the awareness of cognitive bias and encourage adopting multiple perspectives when presented with a claim.